Avoiding WSDL Bad Practices in Code-First Web Services - Ordiales Coscia, José Luis (2011)
Service-Oriented Computing allows software developers to structure applications as a set of standalone and reusable components called services. The common technological choice for materializing these services is Web Services, whose exposed functionality is described by using the Web Services Description Language (WSDL). Methodologically, Web Services are often built by first implementing their behavior and then generating the corresponding WSDL document via automatic tools. Good WSDL designs are crucial to derive reusable Web Services. We found that there is a high correlation between well-known Object- Oriented metrics taken in the code implementing services and the occurrences of the WSDL anti-patterns in their WSDL documents. This paper shows that some refactorings performed early when developing Web Services can greatly improve the quality of generated WSDL documents.